THE EFFECT OF USING FOUR SQUARE METHOD IN WRITING NOTICE TEXT AT THE GRADE VIII OF SMP NEGERI 11 PADANGSIDIMPUAN - Abdul Rahman Siagian (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2019)
The study was conducted at the Grade VIII of SMP Negeri 11 Padangsidimpuan. The aims of this research was to find out if there was a significant Effect of Using four square method on Students’ Writing notice t text at the Grade VIII of SMP Negeri 11 Padangsidimpuan. In order to achieve the purpose of this research, the writer carried out in quantitative approach by applying experimental method. The population of this research was the Grade VIII of SMP Negeri 11 Padangsidimpuan. They were 108 students, the writer used cluster sampling technique to get the sample. The samples were 32 students. The writing notice text was applied as the instrument of this research, the writer used “t” tes formula. Based on the data that has been analyzed, it can be found that (1) the students’ achievement in writing notice text without using four square method was “enough” (65.00), (2) their value by using four square method can be categorized “good” (77.00), and (3) there was a significant effect the result of writing notice text by using four square method. It meant that the hypothesis was accepted.